The impact of histopathological celiac disease activity on dental enamel defects and dental caries - Al-Obaidi, Zainab Q; Radhi , Nada J (Journal of Baghdad College of Dentistry, 2020)
Background: Celiac disease is an autoimmune chronic disease that affects the human’s intestine and subsequently reflects its effect on the entire body health by retardation the absorption and immune mediated complications cause the involvement of oral health. The present study intended to evaluate the impact of the histopathological disease activity upon dental enamel defects and dental caries.Subjects and methods: Forty celiac-diseased patients aged 7-11 years were collected from 3 different teaching hospitals in Baghdad classified by means of the histopathological activity of the intestinal disease according to modified Marsh-Rostami classification. Dental enamel defects were measured by Aine’s classification, while dental caries experience and severity were measured using d1-4mfs/t and D1-4MFS/T.Results: The majority of the sample came with partial villous atrophy of the small intestine (Marsh III-a) and almost half of the sample were with no celiac disease specific dental enamel defects (Aine’s 0), while Aine’s I was the most predominant than Aine’s II. Most missed surfaces due to dental caries in permanent teeth came with Marsh II.Conclusion: The more the severity of celiac disease histopathological activity the more the severity of celiac specific dental enamel defects and the less experienced dental caries.Keywords: Celiac disease, histopathological activity, dental enamel defects, dental caries.